2020
DOI: 10.33271/nvngu/2020-4/076
|View full text |Cite
|
Sign up to set email alerts
|

Impact of water saturation effect on sedimentary rocks strength properties

Abstract: IMpAct of wAter sAturAtIon effect on seDIMentAry rocKs strenGth propertIes purpose. To identify some regularities of reduction in strength of loamy soils and weak sedimentary rocks that are typical for Western Donbas by water saturation condition for assessment of their stability in geotechnologies and forecasting geohazards. Methodology. The paper presents two techniques of experimental testing for sedimentary rocks that allow determining their strength properties under the condition of water saturation. Rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…When exposed to water rocks lose 20-25% of their strength [33]. The coal formation is characterized by monoclinal bedding with the coal bed pitch (the dip angle of coal seam) of 6°.…”
Section: Geological and Geotechnical Conditionsmentioning
confidence: 99%
“…When exposed to water rocks lose 20-25% of their strength [33]. The coal formation is characterized by monoclinal bedding with the coal bed pitch (the dip angle of coal seam) of 6°.…”
Section: Geological and Geotechnical Conditionsmentioning
confidence: 99%
“…Debanjan et al found that shale degraded quickly while sandstone degraded slower until 80% saturation. Babets et al [18] saturated samples first, then dried them, finding that the strength of siltstones and mudstones decreased 1.5-2.5 times in a water-saturated state compared to when air-dried. Hasbollah et al [19] dried and partially soaked shale and sandstone, observing that the tensile strength and anisotropy rose with water content, and more so in shale.…”
Section: Introductionmentioning
confidence: 99%